P217 SACUBITRIL/VALSARTAN IN ADVANCED HEART FAILURE: SAFETY AND EFFECTS ON HAEMODYNAMIC PARAMETERS. (18th May 2022) - Gentile, P; Cantone, R; Perna, E; Ammirati, E; Varrenti, M; D'Angelo, L; Verde, A; Foti, G; Masciocco, G; Garascia, A; Frigerio, M; Cipriani, M
Abstract: Aims: The angiotensin–II receptor neprilysin inhibitor (ARNI), sacubitril/valsartan has been shown to be effective in treatment of patients with heart failure (HF), but limited data is available in patients with advanced disease. This retrospective observational study assessed the effects of ARNI treatment in patients with advanced HF. Methods: We reviewed medical records of all advanced HF patients evaluated at our center for unconventional therapies from September 2016 to January 2019. We studied 44 patients who started ARNI therapy and who had a hemodynamic assessment before beginning ARNI and after 6 ± 2 months. The primary endpoint was variation in pulmonary pressures and filling pressures at 6 months after starting ARNI therapy. Results: Mean patient age was 51.6±7.4 years; 84% were male. At 6±2 months after starting ARNI, there was significant reduction of systolic pulmonary artery pressure (PAP) (32 mmHg, IQR 27–45 vs 25 mmHg, IQR 22.3–36.5; p < 0.0001) and median PAP (20 mmHg, IQR 15.3–29.8 vs 17 mmHg, IQR 13–24.8; p = 0.046). Five of 22 patients (23%) were deferred from the heart transplant (HTx) list because of improvement, while four were listed de novo. After 23 ± 9 months, 3 patients were treated with a left ventricular assist device (LVAD) implantation, while 6 patients underwent Heart transplantation (one in emergency conditions for refractory ventricular tachycardia). Conclusions: Sacubitril/valsartan is effective in reducing filling pressures and pulmonary pressures in patients with advanced HF. The absence of adverse events during follow–up suggests that sacubitril/valsartan is safe and well–tolerated in this cohort of patients.